Peningkatan Hasil Belajar Siswa Dengan Menggunakan Metode Diskusi Pada Mata Pelajaran PAI di SMK Negeri 4 Payakumbuh - Yati, Lefriza (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (IRE) through the implementation of the discussion method in class X of SMK Negeri 4 Payakumbuh. This research uses the Classroom Action Research (CAR) method, conducted in two cycles. Cycle I showed that, although the discussion method was implemented, student activity and learning motivation remained low. However, the test results showed that 52.38% of students achieved completeness. In Cycle II, improvements in the discussion method and student motivation resulted in significant progress, with 52.38% of students achieving completeness and showing better results. The findings suggest continuing the use of the discussion method while improving specific aspects such as time management and providing more effective feedback